Characteristics of Pasteurization Milk Formulated with Ambon Banana Syrup (Musa acuminata colla) at Different Maturity - Devi Dwi Siskawardani; Sukardi Sukardi; Sri Winarsih; Arif Prasetyaji (Food Technology and Halal Science Journal, 2020)
Pasteurized milk defined as fresh cow milk that processed through the heating process with a temperature of 65°C. Generally, pasteurized aimed to prevent the damage of milk due to destructive microorganism (pathogen) activity and able to control nutrition quality. Indonesia banana production in 2016 approximately 7.45  106 t, but only 1.5  106 t were consumed. Banana mostly consumed as fresh fruit or processed as a chip or nugget. This indicated that banana is less treated for a food product. Therefore, the objective of this research was to define the optimum Ambon banana maturity and syrup concentration for producing best-pasteurized milk. This research consisted of two main stages consisted of banana syrup production, and followed by application into pasteurized milk. The nested design was applied, with the main factor was the Ambon banana maturity (115 d, 120 d, and 125 d after flowering), and the sub-factor was banana syrup concentration (5%, 10%, 15%) with three replications. There was a significant effect of banana maturity and syrup concentration on the fat content and aroma of pasteurized milk. In comparison, there was a significant effect of banana syrup on the total dissolved solids (TDS) and total plate count (TPC) of pasteurized milk. The best treatment was 125 d Ambon banana and 15% syrup concentration, with TDS 13.11 °Brix, TPC 8.1  104 CFU mL-1, fat 12.65 %, protein 19.08 %, aroma 3.9 (like), and taste 2.5 (simply delicious).